Malaysian Undergraduates’ Behavioural Intention to Use LMS: An Extended Self-Directed Learning Technology Acceptance Model (SDLTAM) - Ong, Christine Yik Fang Shane (University of Muhammadiyah Prof. DR. HAMKA, 2019)
The usage of Learning Management System (LMS) conducted in Blended Learning style is believed to increase students’ academic performance and their self-directed learning. Nonetheless, the success of students’ behavioural intention to use these e-learning platforms still remains unclear due to factors like self-directed learning, computer self-efficacy, satisfaction and perceived enjoyment and ESL. This preliminary study aims to incorporate factors that impact students’ self-directed learning of English language in achieving behavioural intention to use LMS with an extended model namely, SDLTAM, generalised for the Malaysian educational institutions. The original Technology Acceptance Model 1 by Davis (1989) was used as a theoretical framework of this study. However, the last variable Actual Use was excluded in this study. A sample of 338 respondents from both private and public universities in Malaysia took part in the 48-items survey. The data were analysed through Structural Equation Modelling through SPSS AMOS 24. The SEM AMOS revealed that the factors were found to moderately fit into the proposed model. This could be misspecification within the model and some items within a factor were more correlated to each other than others.